Tetraphenylporphyrin-cobalt(III) bis(1,2-dicarbollide) conjugates: from the solution characteristics to inhibition of HIV protease - Kubát, Pavel; Lang, Kamil; Cígler, Petr; Kožíšek, Milan; Matejicek, Pavel; Janda, Pavel; Zelinger, Zdeněk; Procházka, Karel; Král, Vladimír (The journal of physical chemistry. B, 2007)
Tetraphenylporphyrin conjugates with one (PB1) and four (PB4) cobalt(III) bis(1,2-dicarbollide) substituents were synthesized and the physicochemical and photophysical properties as well as inhibition of HIV-1 protease were described. In methanol, both PB1 and PB4 were monomeric producing the triplet states and singlet oxygen after excitation. The triplet states of PB4 were quickly protonated. Porphyrins exhibited a small decrease of the quantum yields of the singlet oxygen formation (17% for PB4 and 13% for PB1) as compared with 5,10,15,20-tetrakis(4-sulfonatophenyl)porphyrin. On the contrary, no singlet oxygen was detected in aqueous solutions because of strong aggregation. Light scattering and atomic force microscopy (AFM) measurements documented that the behavior of aggregates in aqueous solutions is fairly complex and depends on pH, concentration, and aging. The aggregation started from spherical particles in neutral solutions. In acidic solutions, extended aggregation occurred because of slow protonation of the porphyrin pyrrole nitrogen atoms. Both PB1 and PB4 are new representatives of nonpeptide HIV-1 protease inhibitors. Their activity increased with the increasing number of the cobalt(III) bis(1,2-dicarbollide) substituents and was characterized with the IC50 values of 290+/-44 nM for PB1 and 77+/-13 nM for PB4.
Keywords: financování organizované; mikroskopie atomárních sil; Organometallic Compounds; Inhibitory Concentration 50; Porphyrins; porfyriny; Substrate Specificity; Molecular Structure; inhibitory HIV-proteasy; organokovové sloučeniny; inhibiční koncentrace 50; Boron Compounds; HIV Protease Inhibitors; Models, Molecular; Financing, Organized; molekulární struktura; molekulární modely; HIV Protease; Oxygen; HIV-proteasa; Microscopy, Atomic Force; substrátová specifita; sloučeniny boru; kyslík